Comparative Effectiveness of Traditional Vs. Novel Dressings in Burn Wound Healing: A Systematic Review - Ivanov Radhitya Farid; Rusli Zainuddin (Jurnal Impresi Indonesia, 2026)
This study aims to evaluate the efficacy of traditional dressings compared to contemporary dressings (advanced/novel dressings) in healing burns, using the latest scientific information through the Systematic Literature Review (SLR) methodology. Burns are a global health problem that must be properly addressed to avoid infection, speed up healing, and reduce the risk of long-term complications. Gauze, paraffin, and silver sulfadiazine (SSD) are some of the most commonly used dressings for wounds. However, many studies show that these dressings do not always maintain a moist wound environment, may be painful to change, and can slow down the healing process. In addition to biomaterial manufacturing, advanced dressings such as hydrogels, hydrocolloids, foam dressings, nanofibers, honey-based dressings, and biologically engineered leather have been developed to improve the moist wound environment. This study examined 32 publications published from 2016 to 2025 that met the inclusion criteria according to the PICO methodology. The results showed that advanced dressings consistently accelerated healing time, with some meta-analyses demonstrating a substantial reduction in healing time of up to 4 days compared to SSDs. Additionally, some advanced dressings have now been shown to be superior in preventing bacterial growth, reducing the need for debridement, and lowering pain ratings, especially at the beginning of therapy. However, research still indicates that the efficacy in terms of the quality of scar tissue differs. High costs, limited availability, and the requirement for strict control are major challenges associated with advanced dressings. Overall, the data suggest that advanced dressings are superior to standard dressings for clinical use, but their use should be weighed against healthcare costs and available resources.